Validation of the Korean version of social achievement goals for adolescents: paths from social achievement goals through social behaviour to social adjustment. Issue 4 (2nd October 2018) - Choi, Boungho; Park, Soowon
ABSTRACT: The purpose of this study is to translate and validate the Korean version of the social achievement goals scale, which is known to be a significant variable in predicting social behaviour and social adjustments. There were 133 seventh grade middle school students (male = 64, female = 69) who took part in Study 1, and 425 seventh to eighth grade middle school students (male = 293, female = 132) who participated in Study 2. Explanatory factor analysis of Study 1 revealed that the Korean version of the social achievement goals scale consists of three factors (i.e., social development, demonstration approach, and demonstration avoid goals) with six items for each. Confirmatory factor analysis of Study 2 confirmed the three-factor structure. Latent mean analysis revealed that girls endorsed a higher level of the social development goal, while boys endorsed a higher level of the social demonstration approach goal than girls. No difference was found for the social demonstration avoid goal. The test of criterion-related validity revealed that the social development goal indirectly predicted perceived popularity through prosocial behaviour. The social demonstration approach goal positively predicted aggressive behaviour and perceived popularity, while the social demonstration avoid goal negatively predicted both of them. Taken together, we found that the social achievement goals framework is also applicable to Korean adolescents in the same way as Western samples.